PENGARUH VARIASI TEMPERATUR AIR TERHADAP NILAI KUAT TEKAN BETON - David Daniel Huwae; Abraham Tuanakotta; Tutupoho, Itang; Uneputty, Semuel (Jurusan Teknik Sipil, 2023)
Concrete is a composite material consisting of elements of coarse aggregate, fine aggregate, cement and water which act chemically (hydraulic), which then binds the grains of aggregate together to form a unified concrete (monolith). This study discusses the effect of variations in water temperature of 100C, 200C, and 300C in the concrete mixture on the compressive strength of structural concrete. It is necessary to monitor the temperature of the water in the concrete mixture to reduce excess heat due to the hydration reaction. The water temperature is set according to the design temperature, namely 100C, 200C and 300C to determine the effect on the compressive strength and workability values. Concrete compressive strength testing was carried out at the age of 3, 7 and 14 days. The number of specimens required is 27 cylindrical samples with a diameter of 15 cm and a height of 30 cm. The results of the slump test at water temperatures of 100C, 200C and 300C the lower the water temperature, the lower the slump value. And for testing At the age of 3.7 and 14 days concrete with a temperature of 100C produces Compressive Strength of 10.76 MPa, 12.17 MPa and 13.87 MPa, respectively, a temperature of 200C produces 12.55 MPa, 14.06 MPa and 16.42 Mpa, while the temperature of 300C produces 14.32 Mpa, 16.04 Mpa and 18.12 Mpa. The results of the compressive strength of concrete aged 28 days were converted from the results of the compressive strength test of concrete aged 7 days from the conversion results obtained that the temperature of 100C produced 17.38 Mpa, 200C produced 20.08 Mpa, 300C produced 22.91 Mpa. It can be concluded that normal temperature is more efficient in terms of compressive strength.